Measurement of single-diffractive dijet production in proton-proton collisions at √s=8TeV with the CMS and TOTEM experiments; European Physical Journal C; Vol. 80, iss. 12 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen